Real-world data from the health decision maker perspective. What are we talking about? (Epidemiology, Biostatistics, and Public Health, 2022)
Healthcare decision-makers are increasingly developing policies that seek information on “real-world” data providing “evidence” to support and monitor changes in clinical practice or policy decisions. Many strategies may be evaluated in experimental circumstances, but this does rarely reflect clinical practice. Due to the current focus on information and computer technology to provide safer and more efficient healthcare delivery, the amount of electronic medical records and other electronic healthcare data is increasing exponentially, and these real-world data can be used for evidence generation. This review describes why and how healthcare/policy decision making could benefit from real-world data, it introduces methods to investigate real-world clinical practice, lists potentialities of routinely collected real-world data, reviews their availability in the word, and outlines future challenges in this field.